1984
DOI: 10.3109/02713688408997204
|View full text |Cite
|
Sign up to set email alerts
|

Hematoporphyrin derivative photoradiation induced damage to normal and tumor tissue of the pigmented rabbit eye

Abstract: Cytotoxicity induced by hematoporphyrin derivative (HpD) photoradiation in both normal and experimental tumor tissue of pigmented rabbit eyes has been examined. In addition, documentation of HpD induced fluorescence in ocular structures has also been obtained. Acute normal ocular tissue toxicity studies demonstrated that HpD (1-10 mg HpD/kg) followed 48 hours later by a transpupil irradiation of red light (635 nm, 36-90 J/cm2) resulted in demarcated areas of retinal damage. Long term (chronic) toxicity studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Preclinical studies examined the cytotoxicity induced by hematoporphyrin derivative photoradiation in both normal and experimental tumor tissue in the eye. 1,2 "We looked at distribution and long-term effects of PDT in the eye and thought we were ready to do clinical work using PDT for retinoblastoma and a variety of adult ocular melanomas," revealed Dr. Gomer. The initial clinical results with ocular PDT were disappointing, he admitted.…”
Section: Learning From the Suboptimal Results Of Ocular Pdt For Retinmentioning
confidence: 99%
“…Preclinical studies examined the cytotoxicity induced by hematoporphyrin derivative photoradiation in both normal and experimental tumor tissue in the eye. 1,2 "We looked at distribution and long-term effects of PDT in the eye and thought we were ready to do clinical work using PDT for retinoblastoma and a variety of adult ocular melanomas," revealed Dr. Gomer. The initial clinical results with ocular PDT were disappointing, he admitted.…”
Section: Learning From the Suboptimal Results Of Ocular Pdt For Retinmentioning
confidence: 99%
“…Gomer et al (1984bGomer et al ( , 1985a have studied the effect of PDT on different normal tissues of rabbit's eyes as well as on tumors and concluded that the modality may be safe and effective for the treatment of ocular tumors.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Although RB is highly curable by enucleation and/or radiotherapy, the morbidity of current treatment has made HPD-PDT an appealing prospect in the management of early, and particularly bilateral RB. The relatively easy access of light to the intraocular lesion (Gomer et al, 1984) and documented in-vitro responsiveness of RB to HPD-PDT (Sery, 1979) have encouraged further research.A xenograft model has been developed whereby human RB can be studied heterotransplanted into the anterior chamber of the nude (athymic) mouse eye (Gallie et al, 1977). Necrosis was documented histologically in very advanced tumours after HPD injection followed by PDT in the mouse (Benedict et al, 1980b).…”
mentioning
confidence: 99%
“…Although RB is highly curable by enucleation and/or radiotherapy, the morbidity of current treatment has made HPD-PDT an appealing prospect in the management of early, and particularly bilateral RB. The relatively easy access of light to the intraocular lesion (Gomer et al, 1984) and documented in-vitro responsiveness of RB to HPD-PDT (Sery, 1979) have encouraged further research.…”
mentioning
confidence: 99%